An Amazonian rainforest and its fragments as a laboratory of global change. (30th May 2017) - Laurance, William F.; Camargo, José L. C.; Fearnside, Philip M.; Lovejoy, Thomas E.; Williamson, G. Bruce; Mesquita, Rita C. G.; Meyer, Christoph F. J.; Bobrowiec, Paulo E. D.; Laurance, Susan G. W.
ABSTRACT: We synthesize findings from one of the world's largest and longest‐running experimental investigations, the Biological Dynamics of Forest Fragments Project (BDFFP). Spanning an area of∼ 1000 km 2 in central Amazonia, the BDFFP was initially designed to evaluate the effects of fragment area on rainforest biodiversity and ecological processes. However, over its 38‐year history to date the project has far transcended its original mission, and now focuses more broadly on landscape dynamics, forest regeneration, regional‐ and global‐change phenomena, and their potential interactions and implications for Amazonian forest conservation. The project has yielded a wealth of insights into the ecological and environmental changes in fragmented forests. For instance, many rainforest species are naturally rare and hence are either missing entirely from many fragments or so sparsely represented as to have little chance of long‐term survival. Additionally, edge effects are a prominent driver of fragment dynamics, strongly affecting forest microclimate, tree mortality, carbon storage and a diversity of fauna. Even within our controlled study area, the landscape has been highly dynamic: for example, the matrix of vegetation surrounding fragments has changed markedly over time, succeeding from large cattle pastures or forest clearcuts to secondary regrowth forest. This, in turn, has influenced the dynamics of plant and animal communities and their trajectories of change over time. In general, fauna and flora have responded differently to fragmentation: the most locally extinction‐prone animal species are those that have both large area requirements and low tolerance of the modified habitats surrounding fragments, whereas the most vulnerable plants are those that respond poorly to edge effects or chronic forest disturbances, and that rely on vulnerable animals for seed dispersal or pollination. Relative to intact forests, most fragments are hyperdynamic, with unstable or fluctuating populations of species in response to a variety of external vicissitudes. Rare weather events such as droughts, windstorms and floods have had strong impacts on fragments and left lasting legacies of change. Both forest fragments and the intact forests in our study area appear to be influenced by larger‐scale environmental drivers operating at regional or global scales. These drivers are apparently increasing forest productivity and have led to concerted, widespread increases in forest dynamics and plant growth, shifts in tree‐community composition, and increases in liana (woody vine) abundance. Such large‐scale drivers are likely to interact synergistically with habitat fragmentation, exacerbating its effects for some species and ecological phenomena. Hence, the impacts of fragmentation on Amazonian biodiversity and ecosystem processes appear to be a consequence not only of local site features but also of broader changes occurring at landscape, regional and even global scales.